Taxonomic reassessment of Astragalus phanothrix (Fabaceae): insights from morphological and molecular data - Bagheri, Ali; Maassoumi, Ali Asghar; Blattner, Frank R. (Phytotaxa, 2025)
Astragalus phanothrix has long been a taxonomically controversial species due to conflicting synonymizations and section placements. Originally described under sect. Onobrychium by Bornmüller in 1915, it was later transferred to sect. Hypoglottidei and synonymized with A. saganlugensis. Recent treatments synonymized it with A. cancellatus within sect. Onobrychoidei, highlighting persistent taxonomic ambiguities arising from overlapping morphological characters and the lack of integrative analyses. This study reassessed the taxonomic status of A. phanothrix using morphological examinations and molecular phylogenetic analyses of ITS and matK sequences. Morphological comparisons revealed key diagnostic characters that distinguish A. phanothrix from its putative synonyms. Astragalus phanothrix differs from A. saganlugensis by its mixed black and white hairs on the calyx (compared to erect stems with sparser indumentum), and smaller ovate legumes (compared to larger, elliptic legumes). From A. cancellatus it is separated by the absence of bifurcate calyx hairs, its placement in sect. Hypoglottidei (versus sect. Onobrychoidei), and its predominantly white hairs on the peduncle (compared to mixed black and white hairs). Phylogenetic analyses placed A. phanothrix firmly within sect. Hypoglottidei, supporting its recognition as an independent species. These findings resolve the taxonomic doubts surrounding A. phanothrix, re-establishing it as a distinct species, and highlight the value of integrating morphological and molecular evidence to clarify complex taxonomic relationships in Astragalus.